Isolation of heavy metal resistance bacteria from lake sediment of IIUM, Kuantan - Zainal Abidin, Zaima Azira; Badaruddin, Puteri Nur Ezzati; Khan Chowdhury, Ahmed Jalal (Desalination Publications, 2020)
The present study deals with isolation and identification of heavy metal resistance bacterial strains from lake sediment located within the University of International Islamic University Malaysia (IIUM) campus with the aim to assess possible heavy metal pollution of the lake and in search of bacterial strains that can be utilized for bioremediation purposes. In a total of 80 isolates were obtained and 24 isolates were randomly selected for heavy metal resistance test using the following heavy metals - chromium (Cr), nickel (Ni), copper (Cu), cobalt (Co), cadmium (Cd) and mercury (Hg). Heavy metal resistance pattern associated with IIUM lake was in the form of Cr > Ni > Cu > Co > Cd > Hg. Isolates (I3, I5, I13 and I22) that displayed high heavy metal resistance tests were identified through the 16S rRNA gene sequence. Isolates I3 and I5 were closely related to Bacillus megaterium (99%) and Bacillus cereus (98%) respectively, while Isolate I13 was highly similar to Pseudomonas stutzeri (99%) and I22 I22 fit in Staphylococcus pasteuri (99%).